REFLUX ESOPHAGITIS - BRONCHIAL ASTHMA - ESOPHAGEAL CARCINOMA. PECULIARITIES OF OWN OBSERVATIONS AND LITERARY REVIEW - M. B. Scvortsov (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Reflux esophagitis (R-E) is precancerous condition. The authors show urgency of the problem from the perspective of early detection of reflux esophagitis and its timely surgical treatment considering disappointing results of surgical and radiation and chemotherapy treatments of esophageal carcinoma. Basing on the data of modern literature and own researches the authors claim that late revealing of R-E and late surgery need the treatment of bronchoobstructive and pulmonary complications as well as esophageal carcinoma. Great spread of R-E in Russia and abroad proves the data of own researches. In early diagnostics of R-E the authors pay much attention to described endoscopic criteria of R-E, they are lack the reflex function of the cardia, shortening of the esophagus and other endoscopic signs of complicated forms of R-E. They can serve as guide for timely diagnostics and appointment for surgery. The given clinical observations prove the risk of bronchial complecations and esophageal carcinoma at R-E and show the efficiency of surgical treatment in the case of complications.